Unraveling interactions: Mechanisms shaping the transition of small and medium-sized ports to energy hubs - Negar Safara Nosar (Transportation Research Interdisciplinary Perspectives)
Amid the ongoing climate and energy crises, ports are being urged to embrace the role of low-carbon energy-hubs (EHubs), and small- and medium-sized ports (SMPs) are no exception. While the existing literature primarily focuses on the transition of large ports to EHubs, this paper fills the gap by spotlighting the ongoing transition of two industrial Norwegian SMPs. I conceptualized the SMPs as infrasystem, that is large complex infrastructure system, and I analyzed qualitative data, namely semi-structured interviews and documents.The findings indicate that SMPs transition are shaped by factors beyond ports’ control: technical components, physical infrastructure, and regional material elements, with the Interactions among them being particularly important. Technical interactions within the ports are driven by two mechanisms: the functional coupling, which refers to input–output relations among technical components and physical infrastructures, and (2) the structural coupling, which highlights the conjoint use of material elements. This mechanisms, theoretically, advances our understanding on how multiple systems interact through material elements. Together, these mechanisms lead to varied interactions among similar technologies across different ports, demonstrating that SMP transitions depend heavily on place-specific material contingencies due to limited capacity. The findings challenge the notion of a universal approach to EHub transitions, as effective solutions in one port may fail in another.